1996
DOI: 10.1016/0893-133x(95)00113-r
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Phentermine and Fenfluramine, Alone and in Combination, in Normal, Healthy Volunteers

Abstract: Recent clinical reports indicate that combined administration of phentermine and fenfluramine may have useful effects in the treatment of drug abuse. The present study was designed to evaluate the subjective and mood-altering effects of these drugs, alone and in combination, in normal healthy volunteers. Seven male and five female volunteers participated in an eight-session, double-blind study in which each subject received each of the following drug conditions: d-amphetamine (10 and 20 mg), phentermine (30 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 37 publications
7
41
1
Order By: Relevance
“…It is well accepted that pharmacological treatments leading to increased synaptic 5-HT are not reinforcing. For example, increased serotonergic transmission decreases brain stimulation reward (Harrison and Markou, 2001), produces conditioned place aversions (Marona-Lewicka et al, 1996), and reduces the positive reward value of stimulants both in animals and humans (Brauer et al, 1996;Rea et al, 1998). Thus, in the presence of GBR-type compounds, illicit stimulants such as methamphetamine become very effective 5-HTreleasing agents that lack positive reinforcing qualities.…”
Section: Discussionmentioning
confidence: 99%
“…It is well accepted that pharmacological treatments leading to increased synaptic 5-HT are not reinforcing. For example, increased serotonergic transmission decreases brain stimulation reward (Harrison and Markou, 2001), produces conditioned place aversions (Marona-Lewicka et al, 1996), and reduces the positive reward value of stimulants both in animals and humans (Brauer et al, 1996;Rea et al, 1998). Thus, in the presence of GBR-type compounds, illicit stimulants such as methamphetamine become very effective 5-HTreleasing agents that lack positive reinforcing qualities.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, not all studies were able to show a superior effect of the phen-fen combination on body weight relative to treatment with phentermine or fenfluramine alone (Weintraub et al, 1984;Li et al, 2003). However, there are some indications that the phen-fen combination has a lower abuse potential relative to treatment with phentermine alone (Brauer et al, 1996). In 1996, it is estimated that phen-fen was prescribed to more than 18 million people in the United States (Connolly et al, 1997), and it was in the same year when the FDA approved the use of dexfenfluramine, the d-isomer of fenfluramine, as a chronic treatment of obesity (Colman, 2005) (Fig.…”
Section: The Rainbow Pillsmentioning
confidence: 98%
“…The depletion of 5-HT by medial forebrain bundle lesion with 5,7-dihydroxy-tryptamine seemed to increase the reinforcing efficacy of cocaine in rats (Loh and Roberts, 1990), whereas manipulations that increase CNS 5-HT function can decrease cocaine self-administration (Smith et al, 1986;Carroll et al, 1990;Howell and Byrd, 1995). Studies using coadministered phentermine and fenfluramine as a prototypical DA/5-HT releasing agents demonstrated that compounds that increase both extracellular DA and 5-HT in rat nucleus accumbens are not self-administered by rodents (Glatz et al, 2002), do not induce conditioned place preference in rats (Rea et al, 1998), and have low potential for abuse in human subjects (Brauer et al, 1996). Reinforcing efficacy among a series of cocaine analogs was shown to be negatively related to the SERT potency relative to DAT (Roberts et al, 1999).…”
mentioning
confidence: 99%